Olympic ideals in the social media sphere - Saini, Divya (Πανεπιστήμιο Πελοποννήσου, 2024)
The International Olympic Committee (IOC) has embraced social media as a powerful tool to disseminate the ideals of Olympism and connect with a global audience in the digital age. While enabling the role of sports within the digital age, which plays a significant role to bring about social changes, it also emerged that people expect sport to play an even more proactive part in addressing social challenges. Another common theme was the expectation to continue to commit to action and help to sustainable development goals in United Nations. The Olympic Movement is considered a pioneer amongst the major international sports organizations in terms of development and new technology implementation in communications fields. Thus, it has found a suitable scenario on the internet and social media to spread the Olympic values and ideals amongst the audience. This study presents a comprehensive analysis of the IOC's social media engagement across Twitter (X), LinkedIn, and YouTube from 2012 to 2023, aiming to understand the organization's performance, audience interactions, and the impact of content themes on engagement. Moreover, it investigated the social media strategy and the principles of Olympism and assessed the frequency, themes, and tone of the posts through the social media platforms like Twitter (X), LinkedIn, and YouTube. Further, this study focused on challenges and opportunities in the IOC’s social media dissemination of Olympism and user engagement level and interaction with the IOC's social media content. A study data has been gathered from the selection of social media platforms of Twitter (X), LinkedIn, and YouTube based on several factors like popularity and reach, content variety, interaction on behalf of the users, analysis of tweets, posts due to their likeness to the official account and relevance to the IOC’s communication objectives. By using a mixed method approach of qualitative and quantitative methods, a study result has been analyzed. In this study, the content themes of Promoting Peace and Unity, Advocating Fair Play and Sportsmanship, Empowering Youth and Education, Advancing Gender Equality, Emphasizing Environmental Sustainability, Fostering National Identity and Pride, Leadership, Athlete Success Stories, Industry Insights, Olympic History, Community Engagement, IOC Young Leaders, Behind-the-Scenes, Athlete Interviews, Olympic Legacy, Olympic Torch Relay have been analyzed through qualitative data analysis methods. Further, the quantitative data analysis methods have analyzed the user engagement and interaction with IOC's social media platforms of Twitter (X), LinkedIn, and YouTube. The research findings reveal an upward trend in engagement over the years, with Twitter (X) leading in terms of reach and LinkedIn leading in engagement rate. Content themes play a crucial role in attracting different audiences on each platform, with themes like peace and unity, fair play, and environmental sustainability garnering higher engagement on Twitter (X), and leadership and athlete success stories proving popular on LinkedIn. YouTube's video content, including IOC young leaders and behind-the-scenes footage, effectively engages the general audience and sports fans. Then, by analyzing the social media platforms' engagement rates in social media platforms of Twitter (X), LinkedIn, and YouTube, the majority of people were highly engaged with the social media platform LinkedIn, and the obtained average engagement rate is 9.7%. From the findings of content themes analysis on Twitter (X), LinkedIn, and YouTube, the theme of "Peace and Unity” (35%), “Leadership" (40%), and "IOC Young Leaders (40%)” achieved the highest frequency of post percentages, where these themes provide captivating and engaging content trends with the user that captures the spirit of the Olympic games. Thus, it revealed that by exploring the content themes across the different social media platforms by the IOC, the theme of content "Leadership", and "IOC young leaders" attained the highest percentage. The study identifies implications for the IOC's social media strategy, emphasizing the need for an audience-centric content approach and consistency in content quality. Leveraging video content, promoting positive values, and implementing targeted campaigns are essential for enhancing engagement on all platforms.
Keywords: Ολυμπισμός; Ολυμπιακές αξίες; Διεθνής Ολυμπιακή Επιτροπή; Ηλεκτρονικά κοινωνικά δίκτυα; Μέσα μαζικής ενημέρωσης και αθλητισμός; Κοινωνικά δίκτυα; Διαφήμιση στο Διαδίκτυο; Αθλητισμός - Κοινωνικές απόψεις; Olympism; Olympic values; International Olympic Committee; Online social networks; Mass media and sports; Social networks; Internet advertising; Sports - Social aspects; Digital Olympism; Olympism; Social Media; Engagement; Digital Age; Digital Age in Sports; Linkedin; Facebook; Digitalism in Sports